2019
DOI: 10.1111/jerd.12505
|View full text |Cite|
|
Sign up to set email alerts
|

One‐year bleaching efficacy using two HP products with different pH: A double‐blind randomized clinical trial

Abstract: Objectives This split‐mouth, double‐blind, randomized clinical trial evaluated the 1‐year bleaching efficacy produced by two hydrogen peroxide gels with different pHs. Materials and Methods Twenty‐eight patients were divided into two groups corresponding to two different products: Pola Office (pH = 2.0/SDI) and Pola Office Plus (pH = 7.0/SDI). The treatment was assessed during and after the bleaching procedure up to 12 months post‐treatment. The assessment consisted of two bleaching scales shade guide units (Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 35 publications
1
28
0
9
Order By: Relevance
“…We found that both treatment groups promoted perceptible and acceptable tooth color changes, 31,33 since ∆E ab * and ∆E 00 values were above 50:50% PT and AT thresholds determined by the ISO/TR 28642:2016, 34 where PT and AT thresholds are 1.2 and 2.7 for CIEL*a*b*, and 0.8 and 1.8 for CIEDE2000, respectively 31‐33 . These results were similar to those obtained in studies that found that the pH of 35% (acidic) or 37.5% (neutral) HP whitening gels no influenced in the effectiveness and longevity of in‐office bleaching 7,17 …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We found that both treatment groups promoted perceptible and acceptable tooth color changes, 31,33 since ∆E ab * and ∆E 00 values were above 50:50% PT and AT thresholds determined by the ISO/TR 28642:2016, 34 where PT and AT thresholds are 1.2 and 2.7 for CIEL*a*b*, and 0.8 and 1.8 for CIEDE2000, respectively 31‐33 . These results were similar to those obtained in studies that found that the pH of 35% (acidic) or 37.5% (neutral) HP whitening gels no influenced in the effectiveness and longevity of in‐office bleaching 7,17 …”
Section: Discussionsupporting
confidence: 83%
“…In the present study, shade evaluations were performed objectively with a spectrophotometer which is considered more accurate than visual one 36 . Color differences were calculated using both ∆E ab *, that is the metric more used for evaluate color changes after tooth whitening 2,7,9,11,13,14 and ∆E 00 7,31,33 that shows a better correlation with visual perception than ∆E ab * 31,36 . Regardless of number of bleaching gel changes, it was observed a similar tendency for both color differences formulas (∆E ab * and ∆E 00 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…k L , k C , and k H , the parametric factors, are correction terms for experimental conditions. And finally, R T is a rotation function that accounts for the interaction between chroma and hue differences in the blue region 47,48 …”
Section: Methodsmentioning
confidence: 99%
“…Although some RCTs have already addressed color stability of bleaching protocols, 14–18 none of them have focused on the type of bleaching tray used for the at‐home bleaching. Therefore, this study aimed to evaluate whether the presence of reservoirs may affect color change stability and bleaching sensitivity one‐year after at‐home bleaching.…”
Section: Introductionmentioning
confidence: 99%